Makna Penggunaan Skincare pada Mahasiswa Laki-Laki Analisis Semiotika Roland Barthes di Universitas Islam Negeri Sumatera Utara (UINSU) Medan - Riska Hayati; Rudi Salam; Fakhrur Rozi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to explore the meaning of skincare usage among male students at the State Islamic University of North Sumatra (UINSU) Medan, using a qualitative approach with a descriptive-exploratory design. The study analyzes this social phenomenon through Roland Barthes' semiotic theory, which focuses on how meaning is created and communicated through signs in society. Six key concepts from Barthes' semiotic theory—sign, signifier, signified, denotation, connotation, and myth—are used to analyze how skincare usage is understood within the local context of the students. The research utilizes purposive sampling to select five informants: Imam, Shandy, Iqbal, Septian, and Haikal, all male students at UINSU Medan. Data was collected through in-depth interviews to explore their experiences, motivations, and views on skincare usage, as well as secondary data from literature related to global culture and male skincare. The findings show that the use of skincare among male students at UINSU Medan is influenced by several factors, including beauty standards popularized by the media and global culture, as well as religious values they adhere to. From a semiotic perspective, skincare products can be seen as